The effect of re-used powder on laser metal deposition - Muhammad Arafat Hassan (Nanyang Technological University, 2020)
In the last few decades, emerging growing trend in using Additive Manufacturing (AM) technology was observed, as an alternative to the conventional manufacturing processes. Among the main reasons of this, it could be found the reduce of waste material. In addition, in the absence of AM, the built-up of parts with intricate 3D features would have been unachievable and/or too expensive. However, in AM process such as Laser Metal Deposition (LMD), not all the material involved is used. Issues related with the disposal of the un-used material are still to be completely tackled. As a result, there is a huge loss in the powder consumed and an additional cost incurred in the service provided for the proper disposal of the waste powder. The reuse of the un-melted powder may be one possible solution that can reduce costs and even reduce the environmental impact. There are limited number of studies done on the effects of reusing the powder on LMD process, as there are many concerns related to the integrity and purity of the built parts. This is because the properties of the powder could have been modified during the LMD process from the interaction with the laser. The main objective of the works reported in this document was to study the effects on the reused of powder on LMD process, in particular using Inconel 625 alloy powder. A total of five cycles of deposition were performed, where the powder collected from the previous cycle was reused in the following one. A powder collection system was assembled to trap the powder particles that are deflected away from the melt pool. A morphological and compositional analysis of the reused powder was carried out. The results showed no significant changes in powder morphology with respect to the virgin powder. In addition, the chemical composition of the reused powder from all five cycles showed no significant variations from the chemical composition of the virgin powder. The key findings done on the study of the reused powder as well as the deposited builds will be further discussed in this report.